Specific characteristics of essential oils of four Artemisia species from the Mongolian Trans-Altai Gobi - Javzmaa, N.; Altantsetseg, Sh.; Shatar, S.; Enkhjargal, T.; Anu, Z. (Mongolian Journal of Chemistry, 2016)
The essential oil compositions of four Artemisia species in Mongolian Trans-Altai Gobi were studied by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS). The oil from A.macrocephala Jacq and A.dracunculus Ledeb. were characterized by the presence of monoterpene hydrocarbons and oxygenated monoterpeneoids predominately. E-nerolidol (26.95%), methyleugenol (23.29%) and sabinene (13.21%) were found as main components in the essential oils of A.dracunculus. A.macrocephalla was characterized by the presence of chamazulene (13.8%), cineol (11.7%), myrcene (9.0%), germacrene-D (7.1%). A.anethifolia Web was characterized by the presence of fragrant compounds as camphor (26.05%), α-thujone (10.1%), borneol (5.1%). Davanone and davanone derivatives were also detected in the sample in amount of 7.7% in total. A.scoparia Waldst differed by domination of monoterpene hydrocarbons (78.9%) with (Z)- β-ocimene (29.24%), α-pinene (15.19%), limonene (10.27%) and myrcene (9.61%). Mongolian Journal of Chemistry 16 (42), 2015, 34-38